SOSIALISASI PENCEGAHAN DAN PENANGGULANGAN TBC PADA PEKERJA HOME INDUSTRI BATIK DI KALURAHAN WIJIREJO, KAPANEWON PANDAK, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Santjoko, Herman; Kasjono, Heru Subaris; Yamtana, Yamtana; Primiaji, Primiaji; Widarto, Elvi Sandra; Putri, Haqifa Rosyida (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
TB plays an important role in cases of death and morbidity due to respiratory tract infections. Global TB Report 2022, TB cases in Indonesia are in 2nd place in the world after India. The estimated number of cases recorded reached 969 thousand with a case notification figure of 443,235. Based on the estimated number of cases, only 45.7% have been found and treated. This means that 54.2% of TB cases are still undetected and pose a risk of infecting other people. TB can attack anyone, including workers who have a fairly high level of vulnerability. Based on age group, the age range most affected by TB is 15-54 years or the productive age group. The characteristics of the productive age group are high mobility and gradual exposure to TB bacteria which may occur without being noticed. TB cases in Indonesia in 2022 will be recorded at 717,941 cases. This number jumped 61.98 percent from the previous year which was 443,235 cases